Developing an Approach Based on Behavioral Objectives to Estimate the Cut-off Score: A Comparison with Angoff's Method - Audeh, Ahmad; Shraim, Ahmad (Jordan Journal of Educational Sciences, 2010)
This study aimed at developing an approach based on behavioral objectives to estimate the cut-off score compared with Angoff's method, which determines the cut-off score based on testitems. In order to achieve this aim a content domain was selected, well defined, and analyzed by translation this content into a set of behavioral objectives. Every objective in the set was followed by a group of multiple-choice items, which measure this objective to enable the raters to estimate the cut-off score for every objective. Two test forms were constructed using two procedures of selecting items for each form based on item-objective congruence for one form, and random selection for the other one.A total group of 30 raters estimated the cut-score of each objective and item in the two test forms. The raters were classified according to their educational qualifications and work status into three equal groups. Two of the three groups estimated the cut-off scores using Angoff's method, two times or rounds over a period of two weeks. A sample of 171 ninth grade students were tested immediately after they had completed studying the unit in order to calculate the statistical indices of the students and the items, for validating the cut-off scores and for comparison purposes.The results of the study indicated that the cut-off score based on objectives was (0.56) in the two raters' rounds, while it was (0.67) for the first form using Angoff's method in the first round, (0.66) in the second round, and (0.63) for the second form in the two rounds. Furthermore, all correlation coefficients between the raters' estimations in the two rounds were high (0.93; 0.96) and were statistically significant at (α = 0.01). The results also indicated that there was no statistically significant difference between the reliability coefficients of the two methods (objective-based and test-item-based) of estimating cut-off scores.The results of the study also indicated that there was no statistically significant difference between the estimated cut-off scores by the raters in the three groups based on the behavioral objectives. The two methods were high and equivalent statistically of two reliability indices (Hit rate, and Kappa coefficient); but they were significantly different in their ability to predict a student’s school achievement in favor of the objective-based method. The study concludes that the objective-based method is superior in estimating cut-off scores compared with the most frequently used testitem- based method; it is more efficient in predictive validity, more powerful and universal due to the strong-grounded early steps starting specifying the content domain, and the population of behavioral objectives representing this domain